Analisis konten diskusi publik mengenai program Makan Bergizi Gratis (MBG) pada platform X (Twitter) periode April 2025 - Lia Puspitasari; Yama Pradhana Sumbodo; Rofi’ah Rofi’ah (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
The Free Nutritious Meal Program implemented by the Indonesian government in April 2025 triggered intense public discussion on the social media platform X (formerly Twitter), reflecting a sharp polarization of opinions between support and criticism. This study aims to analyze the forms, sentiment directions, and network structure of public discourse surrounding the MBG program in digital space. A quantitative descriptive approach was employed, combining content analysis and Social Network Analysis (SNA) based on social media data. Data were collected through web crawling using Python 3 on Google Colab, yielding 33,213 tweets posted between 1-30 April 2025. The analysis classified public sentiment (positive and negative) and mapped user interactions to identify communication patterns and key actors. The findings reveal two dominant clusters: pro and critical groups. The pro program cluster was dominated by institutional and buzzer accounts with uniform narratives, while the critical cluster consisted mainly of personal accounts expressing participatory and argumentative views highlighting issues of implementation, food quality, and alleged budget irregularities. The network mapping shows two major clusters with limited interaction, indicating digital polarization and the echo chamber phenomenon. Conceptually, the study demonstrates that public opinion formation on social media is shaped not only by policy substance but also by political communication strategies and platform algorithms that amplify dominant narratives. These findings imply the need for a two-way, participatory communication strategy and improved digital literacy to foster a healthier and more deliberative public discourse in Indonesia’s digital sphere.